Damaging democracy? Security provision and turnout in Afghan elections†. (13th January 2019) - Condra, Luke N.; Callen, Michael; Iyengar, Radha K.; Long, James D.; Shapiro, Jacob N.
Abstract: In emerging democracies, elections are encouraged as a route to democratization. However, not only does violence often threaten these elections, but citizens often view as corrupt the security forces deployed to combat violence. We examine the effects of such security provision. In Afghanistan's 2010 parliamentary election, polling centers with similar histories of pre‐election violence unintentionally received different deployments of the Afghan National Police, enabling identification of police's effects on turnout. Using data from the universe of polling sites and various household surveys, data usually unavailable in conflict settings, we estimate increases in police presence decreased voter turnout by an average of 30%. Our results adjudicate between competing theoretical mechanisms through which security forces could affect turnout, and show behavior is not driven by voter anticipation of election‐day violence. This highlights a pitfall for building government legitimacy via elections in weakly institutionalized and conflict‐affected states.